(untitled) (Eurasian Journal of Ecology, 2016)
There is a brief generic and specific analysis by the family Asteraceae, which is the basis of urban flora of Almaty in this article. Floristic researches were performed in accordance with conventional methods by Skvortsov. Collecting of herbarium was carried out in different areas of the city: 1) Central Park of Culture and Rest 2) Park named 28 guardsmen, 3) a park named the First President (above Orbit microdistrict), 4) Femeli Park in the 4th microdistrict, 5) Park in Almalinsky district (square street Shevchenko Zhambyla-Zharokov-Morris Torrez 6) park area near the microdistrict Kulager 7) the grove named Baum and several dozen public gardens. Besides this collecting of herbarium was conducted in other urban areas by the direction from north to south and from east to west. During herbarium collecting ecologic map and a schematic map of the city of Almaty has been used. In determining of plants were used the "Flora of Kazakhstan" and "Illustrated determinant of the plants of Kazakhstan."